Can Market-Oriented Environmental Regulation Tools Improve Green Total Factor Energy Efficiency? Analyzing the Emission Trading System - Wang, Xingshuai; Tang, Shida; Ahmad, Mahmood; Bai, Yang (Frontiers in Environmental Science, 2022)
Undoubtedly, green total factor energy efficiency plays a pivotal role in achieving energy conservation, emission reduction, and green development goals. China mainly used command-based environmental regulation tools to enhance the green total factor energy efficiency in the early stage. Later, under the new trend of market-oriented reform, the Chinese government introduced market-oriented environmental regulation tools such as carbon rights. However, the effectiveness of market-oriented environmental regulation tools is still unclear. Therefore, this study investigates the impact of market-oriented environmental regulation tools on green total factor energy efficiency by using the data of 265 cities in China. For this purpose, yearly data from 2003 to 2017 is employed using the difference-in-difference method. The empirical results unveil that the emission trading system can significantly improve green all factor energy efficiency. In addition, the heterogeneity analysis shows that the emission trading system is conducive to improving energy efficiency in resource-based cities. Based on the results, this study provides policy enlightenment for market-oriented environmental regulation tools to promote green development according to local conditions.